RANCANGAN ULANG TATA LETAK PABRIK DENGAN MENGGUNAKAN BLOCPLAN (STUDI KASUS DI UD.ROTI JAMAL) - Abdul Azis Syarif; Rini Oktaviani Bedros (Universitas Quality, 2018)
This research is motivated by the problem of production area condition in UD. Jamal bread and irregular work facilities. This is, seen in operators working in empty areas and the laying of baking pans that almost fill the work area and placed carelessly (uncluttered) at the bottom of the production floor. The purpose of this research is to design the layout and work facilities by combining BLOCPLAN so that operators work comfortably, safely, and healthy in doing their work. The proposed improvement plan is the layout design with BLOCPLAN taking into account the placement of the proposed work facility design. There are 3 (three) designed proposed facilities that are used for empty pan, baking rack used for baking sheet, as well as frying pan. the total displacement moment occurring in the layout design and the proposed facility is 1178 meters displacement / day, then there is a decrease in total displacement moment of 4088.4 meters displacement / day.